Bangkit Lebih Cepat: Melalui Program Pendampingan SDM dan Perencanaan Usaha Dengan Memanfaatkan Aplikasi Marketplace di Masa Pasca Pandemi Covid-19 pada Toko Sembako “Winda Jaya” Surabaya - Suryati Eko Putro; Novie Noordiana R.Y; Totok Mardianto; Arlisa Indriawati; Siti Khasanaturrohmah; Yeriko Yosua A (Institut Nalanda, 2023)
As a result of the Covid-19 pandemic that hit Indonesia in 2020, it has resulted in a decline in the economy and activities in various sectors and regions of Indonesia. In 2023, the economic condition, which was in shock due to the Covid-19 pandemic, is gradually improving in line with the stability of the domestic financial market and the stretching of several economic sectors. The Government of Indonesia has declared that this year our economy must recover more quickly by making policy steps to strengthen the economy accompanied by transparent prioritization and proper policy coordination and synchronization. The community service team at the Faculty of Economics and Business, Surabaya University of Technology feels compelled to participate in the success of government programs by creating HR assistance programs and business planning by utilizing marketplace applications in the post-Covid-19 pandemic for business development and increasing sales turnover. The accompanying partner this time is the